Manganese oxides supported on ACFN by a one‐step redox method for the low‐temperature NOx reduction with NH3: effect of acid addition. Issue 5 (22nd January 2020) - Tang, Xiaolong; Gu, Tian; Yi, Honghong; Zhao, Shunzheng; Gao, Fengyu; Zhang, Runcao; Wang, Yuhe
Abstract: BACKGROUND: In this study, manganese dioxide (MnO2 ) was formed in situ on the surface of ACFN (nitric acid modified activated carbon fibres) by a one‐step redox method for the selective catalytic reduction (SCR) of nitric oxides (NOx) with ammonia (NH3 ) at low temperature. Meanwhile, the water and sulfur dioxide (H2 O and SO2 ) deactivation mechanism were investigated. RESULTS: Each acid, including hydrochloric, nitric and acetic (HCl, HNO3 and CH3 COOH), released H + in solution at different rates, which lead to distinct pH environments. As the driving force, it has an effect on the redox reaction, resulting in the different MnO2 amount and performance of the MnO2 /ACFN catalysts. The MnO2 /ACFN (CH3 COOH) catalyst exhibited good NH3 ‐SCR activity, water resistance and sulfur resistance. CONCLUSION: The MnO2 /ACFN (CH3 COOH) catalyst showed 3D growth and uniform distribution of MnO2 sheets on the surface of the support, which resulted in a larger specific surface area and better redox properties. The CH3 COOH can gradually decompose H + so that H + is given priority to internal diffusion. The redox reaction preferentially took place in the interior, thereby promoting the formation of more MnO2, which is beneficial to the NH3 ‐SCR reaction. © 2019 Society of Chemical Industry